Amoeboid–mesenchymal transition and the proteolytic control of cancer invasion plasticity - Adam W. Olson; Jonathan Li; Xiao-Yan Li; Lana King; Long Jiang; Kalins Banerjee; Atticus J. McCoy; Mahnoor N. Gondal; Arul M. Chinnaiyan; Dorraya El-Ashry; Evan T. Keller; Andrew J. Putnam; et al. (Proceedings of the National Academy of Sciences, 2026)
Invasion plasticity allows malignant cells to toggle between collective, mesenchymal, and amoeboid phenotypes while traversing extracellular matrix (ECM) barriers. Current dogma holds that collective and mesenchymal invasion programs trigger the mobilization of proteinases that digest structural barriers dominated by type I collagen, while amoeboid activity allows cancer cells to marshal mechanical forces to traverse tissues independently of ECM proteolysis. Here, we use cancer spheroid-3-dimensional matrix models, single-cell RNA sequencing, and human tissue explants to identify the mechanisms controlling mesenchymal versus amoeboid invasion. Unexpectedly, collective/mesenchymal- and amoeboid-type invasion programs—though distinct—are each characterized by active tunneling through ECM barriers, with expression of matrix-degradative metalloproteinases. CRISPR/Cas9-mediated targeting of a single membrane-anchored collagenase, MMP14/MT1-MMP, ablates tissue-invasive activity while coregulating cancer cell transcriptional programs. Though changes in matrix architecture, nuclear rigidity, and metabolic stress as well as the presence of cancer-associated fibroblasts are proposed to support amoeboid activity, none of these changes restore invasive activity of MMP14-targeted cancer cells. While a requirement for MMP14 is bypassed in low-density collagen hydrogels, invasion by the proteinase-deleted cells is associated with nuclear envelope and DNA damage, highlighting a proteolytic requirement for maintaining nuclear integrity. Nevertheless, when cancer cells confront explants of live human breast tissue, MMP14 is again required to support invasive activity. Corroborating these results, spatial transcriptomic and immunohistological analyses of human breast cancers identified MMP14 expression in tissue-infiltrating carcinoma cells that were further juxtaposed with proteolyzed type I collagen fragments, underlining the pathophysiologic importance of this proteinase in directing invasive activity in vivo.